Multispecies biofilm removal by XP-endo Finisher and passive ultrasonic irrigation: A scanning electron microscopy study - Teves, Abel; Blanco, Daniel; Casaretto, Mario; Torres, John; Alvarado, Débora E.; Coaguila-Llerena, Hernán [UNESP]; Faria, Gisele [UNESP]; Jaramillo, David E. (Wiley, 2021)
The aim was to assess the effect of XP-endo Finisher (XPF) on multispecies biofilm removal, in comparison with passive ultrasonic irrigation (PUI) and conventional syringe irrigation (CSI), by scanning electron microscope (SEM). Fifty mandibular first premolars were instrumented, longitudinally sectioned. The split halves were incubated for 4 days with a broth obtained from three bacteria strains: Enterococcus faecalis, Eikenella corrodens and Streptococcus anginosus. Subsequently, the re-approximated split halves were irrigated with 4% sodium hypochlorite (NaOCl) or water using CSI, and the final irrigation protocols were CSI with 4% NaOCl (CSI+4%NaOCl), PUI+4%NaOCl, XPF+4%NaOCl and CSI+water. The analysis of biofilm removal was performed using SEM images. There were no differences between PUI and XPF (P > 0.05), and both groups promoted higher biofilm removal than CSI+4%NaOCl and CSI+water groups (P < 0.05). It can be concluded the multispecies biofilm removal was significantly improved using XPF and PUI when compared to CSI.
Keywords: biofilm; passive ultrasonic irrigation; root canal treatment; scanning electron microscopy; sodium hypochlorite; XP-endo Finisher